Relationship Between Word of Mouth (WOM) Communication and Brand Equity of Sport Products Among Consumers in Kuantan, Pahang - Abdul Latif, Rozita; Ramli, Norlina; Mohamed Alauddin, Aishah Nadirah (International Journal of Social Sciences and Management, 2019)
The main purpose of this study was to determine the relationship between word of mouth (WOM) communication and brand equity of sport products among consumers in Kuantan, Pahang. Four hundred and sixty-one consumers from Kuantan, Pahang participated in the study. Participants completed WOM communication questionnaires originally designed by Uslu et al. (2013), and the brand equity questionnaire originally designed by Yoo and Donthu (2001) and Lassar et al. (1995). The results showed high level of WOM communication of mean of 3.56 and (SD= .72) and the brand equity dimensions indicated highest mean on “perceived quality” 3.73 with (SD= .63). The r-value was (p<.487) and it indicated a significant positive relationship between WOM communication and brand equity. The findings of the study provide theory and understanding for marketers in influencing consumers to have positive WOM communication and brand equity towards sports brands. Int. J. Soc. Sc. Manage. Vol. 6, Issue-2: 28-34